Mendelian randomization study shows no causal relationship between psychiatric disorders and glaucoma in European and East Asian populations - Zhang, Yan; Fu, Longhui; Feng, Fang; Liu, Bo; Lei, Ying; Kang, Qianyan (Frontiers in Genetics, 2024)
Background: Glaucoma is a leading cause of blindness strongly associated with psychiatric disorders, but the causal association between glaucoma and psychiatric disorders remains uncertain because of the susceptibility of observational studies to confounding and reverse causation. This study aims to explore the potential causal association between glaucoma and three highly related psychiatric disorders (Depression, Insomnia, and Schizophrenia) in the European and East Asian populations using a two-sample Mendelian randomization analysis. Methods: Instrumental variables (IVs) of depression, insomnia, and schizophrenia in the European population were obtained after strict filtering. Summary-level data for glaucoma and glaucoma subtypes (primary open-angle glaucoma and primary closed-angle glaucoma) were obtained as outcomes. The inverse variance weighting (IVW) method was used as the primary method. Additionally, the causal effect was evaluated in the East Asian population using the same methods to validate analysis results. The robustness of these results was confirmed using heterogeneity, pleiotropy, and Steiger directionality test. Results: The primary MR results indicated that genetically driven psychiatric disorders were not causally associated with glaucoma (Depression: odds ratio (OR): 1.15, 95% confidence interval (CI): 0.93–1.42, p = 0.20; Insomnia: OR: 1.14, 95% CI: 0.63–2.05, p = 0.66; Schizophrenia: OR: 1.00, 95% CI: 0.93–1.08, p = 0.95), either with the risk of glaucoma subtypes in the European population. Meanwhile, results in the East Asian population were consistent with the results among the European population (Depression: OR = 1.38, CI 0.75–2.53, p = 0.30; Insomnia: OR = 0.99, CI 0.83–1.18, p = 0.93; Schizophrenia: OR = 1.06, CI 0.94–1.20, p = 0.34) with similar causal estimates in direction. Consistency was obtained by corroborating with other supporting methods. Besides, the robustness of the results was proved and the directionality test confirmed our estimation of potential causal direction (p < 0.001). Conclusion: This study found a non-causal association between psychiatric disorders and the risk of glaucoma in the European and East Asian populations, which contradicts many existing observational reports, indicating that increased psychiatric disorders in glaucoma patients were more likely modifiable rather not inheritable.